"Familien in Deutschland" - FiD: Enhancing research on families in Germany - Mathis Schröder; Rainer Siegers; C. Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The full range of public benefits for married people and families is being evaluated on behalf of the German Federal Ministry for Family Affairs, Senior Citizens, Women and Youth (BMFSFJ) and the German Federal Ministry of Finance (BMF) for the first time. To strengthen existing datasets such as the Socio-economic Panel (SOEP) in their statistical power, Familien in Deutschland (FiD) was initiated. FiD is one of the related studies of the SOEP, i.e. a data collection effort closely related to the SOEP in concepts and contents. The main difference lies in the sample, as FiD provides information on families only, specifically on single parents, large families, low-income families, and families with very young children. These groups are main targets of family policies but their numbers in regular surveys such as the SOEP are too small to conduct meaningful statistical analyses. This paper provides an overview of the sampling concepts and questionnaire contents in FiD, along with case numbers and quality indicators for the first three waves of data collection from 2010 to 2012.
Keywords: 330